21st Century Leadership as a Catalyst for Sustainable Reform: Transformative Practices in Digital Education - Moses Adeleke Adeoye; Rasheedat Modupe Oladimeji; Oyeronke Christiana Paramole (Universitas Islam Bunga Bangsa Cirebon, 2024)
In the rapidly evolving landscape of education, integrating digital technologies is essential for enhancing teaching and learning outcomes. However, successful implementation relies heavily on effective leadership. This research investigates the role of leadership, particularly transformational leadership, in facilitating digital integration within educational contexts. Employing a qualitative research approach, the study engaged school leaders—specifically principals and vice principals—from 30 institutions. The methodology utilised a thought experimental scenarios approach alongside a relevant literature review to gather insights into the experiences and perceptions of these leaders regarding leadership practices and change management processes. The findings reveal that transformational leadership significantly influences the successful adoption of digital technologies by fostering a culture of collaboration and innovation. Leaders who embody transformational qualities, such as inspiration and individualised support, effectively engage educators and promote a shared vision for digital integration. Additionally, the research highlights the importance of structured change management processes in guiding the implementation of digital initiatives, ensuring stakeholder engagement and continuous evaluation. In conclusion, this study underscores the critical role of leadership in navigating the complexities of digital integration in education. It contributes to the existing body of knowledge by providing a comprehensive theoretical framework that integrates transformational leadership, change management, and constructivist learning theories. The insights gained from this research offer practical recommendations for educational leaders, emphasising the need for ongoing professional development and stakeholder collaboration to sustain successful digital transformation in academic settings.